Pola Honorifik Undak-Usuk Keigo Bahasa Jepang yang Mencerminkan Nilai Uchi-Soto sebagai Wujud Identifikasi Kelompok - Astami, Timur Sri (Bina Nusantara University, 2010)
The Japanese has not became a product only, but it becomes more than language product activity, but still relates to culture. Article presents Keigo which is is different from sonkeigo, kenjougo and teineigo. Therefore using keigo such as language user depends on uchi soto and ue shita factors. If using sonkeigo such as opponent more higher than speaker position. Oppenent position as me ue (higher position level) and soto no mono (outsider). And than using kenjougo such as speaker more lower than opponent position. Speaker as uchi (insider) or me shita (low position level).